Dinamika Politik Pemerintah Desa Adat Intaran Bali dalam Penanggulangan Pandemi Covid-19 - Revina Nanda Amalia; Muhammad Irvan Maulana; Muhammad Raihan Primatama (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The COVID-19 pandemic has become an event that has had very significant impacts on humans in various aspects of life. The paradigm shift in social, political, and economic life forces people to adapt quickly because of it. In Indonesia itself, the economic paralysis is seen explicitly from various regions that rely on tourism as the center of their economy. Bali, for example, as one of the provinces in Indonesia that relies on tourism as a driving force for the community's economy, has made it the province most affected by the pandemic. Bali is a province that still firmly holds the nobility of adat as an inseparable part of people's lives. The nobility of Balinese customs is found in the uniqueness of the government system in which there are two differentiations of the village structure, namely the Traditional Village or Pakraman Village or Desa Adat and the Administrative Village. Traditional Villages in Bali have the autonomy to regulate their territory and govern their citizens. This autonomy can be seen in one of the existing traditional villages, namely the Desa Adat Intaran. At the beginning of the COVID-19 pandemic, the Desa Adat Intaran imposed customary regulations or pararem to prevent the increase in COVID-19 cases in the village. This pararem applies to villagers as well as outside villagers who want to visit the Desa Adat Intaran area. In this article, we will examine the political dynamics that occurred during the process of handling the COVID-19 pandemic, ranging from conflicts that occurred, power imbalances, community resilience, networks, to the psychology of rural communities related to the postcolonial adaptation process. The use of descriptive qualitative methods with the main data sources from interviews and observations and literature review as secondary data was chosen in this article. This article produces a research hypothesis that the dynamics of handling COVID-19 in the Desa Adat Intaran is a form of response to historical events, conflicts, and the identity of local wisdom that are integrated into one another.